Bilateral same-session flexible ureterorenoscopy for renal and/or ureteric stone disease treatment - Ersan Arda (Taylor & Francis Group, 2018)
Objective: To evaluate the effectiveness and safety of bilateral same-session flexible ureterorenoscopy (f-URS) in the treatment of bilateral renal and/or ureteric stone disease. Patients and methods: From October 2007 to December 2015, 62 patients who had undergone bilateral, same-session f-URS were included in the study. The procedures were performed under general anaesthesia, in lithotomy, and initiated on the side in which the patient was clinically symptomatic or on the side in which the stone was smaller. Plain abdominal radiography, intravenous urography, renal ultrasonography and/or non-contrast computed tomography scans were conducted in all patients. The success rate was defined as, patients who were stone-free or only had residual fragments of <3 mm. Results: A total of 62 patients (43 male, 19 female), with a mean (SD) age of 39 (15.1) years, were included. The mean (SD) stone size was 23.2 (6.11) mm with a mean (SD) operative time of 58.8 (16.24) min. The stone-free rates were 90.3% and 100% after the first and second procedures, respectively. The mean (SD) hospital stay was 1.58 (0.72) days. There were minor complications (Clavien–Dindo grade I–II) in 10 (16%) patients and major complications (Clavien–Dindo III–IV), e.g. distal ureter laceration and laser injury of the ureter, in two patients. Conclusion: Same session bilateral f-URS is a successful and safe method for bilateral renal and/or ureteric stones. Keywords: Flexible ureterorenoscopy, Bilateral, Renal stones, Ureteric stones